Download as pptx, pdf, or txt
Download as pptx, pdf, or txt
You are on page 1of 41

APPLİCATION OF BOOLEAN

ALGEABRA

CHAPTER 4

Prof. Dr. Mehmet Akbaba

Prof. Mehmet Akbaba Digital Logic 1


Multiplying Out and Factoring Expressions
Given an expression in product-of-sums form, the
corresponding sum-of-products expression can be
obtained by multiplying out, using the two distributive
laws:
X(Y + Z) = XY + XZ (4-1)
(X + Y)(X + Z) = X + YZ (4-2)

In addition, the following theorem is very useful for


factoring and multiplying out
(X + Y)(X' +Z) = XZ + X'Y (4.3)
Note that the variable that is paired with X on one side of
the equation is paired with X' on the other side, and vice
versa.

Prof. Mehmet Akbaba Digital Logic 2


Proof:
If X = 0, (3-3) reduces to Y(1 + Z) = 0 + 1 . Y or Y = Y
If X = 1, (3-3) reduces to (1 + Y)Z = Z + 0 . Y or Z = Z.
Because the equation is valid for both X = 0 and X = 1, it
is always valid.
The following example illustrates the use of Theorem
(3-3) for factoring:

AB+A'C = (A + C)(A' + B)

Note that the theorem can be applied when we have two


terms, one which contains a variable and another which
contains its complement.

Prof. Mehmet Akbaba Digital Logic 3


Theorem (3-3) is very useful for multiplying out
expressions. In the following example, we can apply
(3-3) because one factor contains the variable Q, and the
other factor contains Q'.
(Q + AB')(CD+ Q') = QCD + Q'AB'

If we simply multiplied out by using the distributive law,


we would get four terms instead of two:
(Q + AB')(CD + Q') = QCD + QQ' + AB'CD + AB'Q'

Because the term A B' C D is difficult to eliminate, it is


much better to use (3-3)instead of the distributive law.

Prof. Mehmet Akbaba Digital Logic 4


In general, when we multiply out an expression, we
should use (4-3) along with (4-1) and (4-2). To avoid
generating unnecessary terms when multiplying out,
(4-2) and (4-3) should generally be applied before (4-1),
and terms should be grouped to expedite their
application. [(X+A)(X+B)=X+AB, (X+A)(X’+A)=XA+X’A]

What theorem was used to eliminate ABC? (Hint: let X


= AC.)

Prof. Mehmet Akbaba Digital Logic 5


In this example, if the ordinary distributive law (4-1)
had been used to multiply out the expression by brute
force, 162 terms would have been generated, and 158
of these terms would then have to be eliminated.

Prof. Mehmet Akbaba Digital Logic 6


Example of Factoring
The same theorems that are useful for multiplying out
expressions are useful for factoring. By repeatedly
applying (4-1), (4-2), and (4-3), any expression can be
converted to a product-of-sums (POS) form.

Prof. Mehmet Akbaba Digital Logic 7


= (A + B + C’DE)(A + C‘DE + D' + E)(A' + C)
=(A+B+C’)(A+B+DE)(A+D’+E)(A’+C)
= (A + B + C’)(A + B + D)(A + B + E)(A + D' + E)(A' + C) (4-5;
This is the same expression we started with in (4-4).

Prof. Mehmet Akbaba Digital Logic 8


Exclusive-OR (EX-OR) Operations
or EX-OR GATE

The exclusive-OR operation ( ) is defined as follows:

0 0=0 0 1=1 1 1=0


1 0=1
The truth table for X Y is

Prof. Mehmet Akbaba Digital Logic 9


The truth table for X Y is

X Y X Y
0 0 0
0 1 1
1 0 1
1 1 0

EX-OR GATE SYMBOL

Prof. Mehmet Akbaba Digital Logic 10


Prof. Mehmet Akbaba Digital Logic 11
From this table, we can see that X Y = 1 iff X = 1
anad Y=0 or X=0 and Y = 1, but not both =1.

The ordinary OR operation, which we have previously


defined, is sometimes called
inclusive OR because X + Y = 1 iff X = 1 or Y = 1, or
both.
Exclusive OR can be expressed in terms of AND and
OR. Because X Y = 1
iff X is 0 and Y is 1 or X is 1 and Y is 0, we can write
X Y = X' Y + XY' (4.6)
,

Prof. Mehmet Akbaba Digital Logic 12


X Y = (X + Y)(XY)' = (X + Y)(X' + Y') = X' Y + XY' (4.7)

In (4-7), note that (X Y)' = 1 if X and Y are not both 1.

We will use the following symbol for an exclusive-OR


gate:

Prof. Mehmet Akbaba Digital Logic 13


The following theorems apply to exclusive OR

X 0=X X 1=X’
X X=0 X X’=1
X Y=Y X (commutative law)
(X Y) Z = X (Y Z)=X Y Z
(Associative law)
X(Y Z)= XY XZ (Distributive law)
(X Y)’=X Y’=X’ Y=X’Y’+XY
Prof. Mehmet Akbaba Digital Logic 14
Any of these theorems can be proved by using a truth
table or by replacing X Y with one of the equivalent
expressions from Equation (4-7). Proof of the
distributive law follows:
XY XZ=XY(XZ)’+(XY)’XZ=XY(X’+Z’)+(X’+Y’)XZ
=XYZ’+XY’Z
=X(YZ’+Y’Z)=X(Y Z)

Prof. Mehmet Akbaba Digital Logic 15


EQUIVALENT OR EX-NOR OPERATION
OR EX-NOR GATE
The equivalence operation ( ) or EX-NOR

operation (or EX-NOR GATE) is defined by truth table:

EX-NOR=(EX-OR)’ (4.8)
Therefore EX-NOR is defined
As complement (NOT)
of EX-OR

Prof. Mehmet Akbaba Digital Logic 16


(4.9)

Prof. Mehmet Akbaba Digital Logic 17


Prof. Mehmet Akbaba Digital Logic 18
Just as for exclusive-OR, the equivalence (EX-NOR )
operation is commutative and associative.

We will use the following symbol for an equivalence gate:

Or another notation is EX-NOR GATE shown


below

AB

Prof. Mehmet Akbaba Digital Logic 19


Because equivalence is the complement of exclusive-OR,
an alternate symbol for the equivalence gate is an
exclusive-OR gate with a complemented output:

(A B)’=(A  B)

F=(A’B  C)+(B AC’)

Prof. Mehmet Akbaba Digital Logic 20


EX-NOR=(EX-OR)’
A  B= (A  B)’=(AB’+A’B)’ = (A’+B)(A+B’)
=A’A+A’B’+AB+BB’= A’B’+AB

Prof. Mehmet Akbaba Digital Logic 21


Example 1 (Örnek 1)
Open the following expression
(Aşağıdaki ifadeyi açınız)

F=(A’B  C)+(B’  AC’) =

Prof. Mehmet Akbaba Digital Logic 22


Example 2 (Örnek 2)
Open the following expression
(Aşağıdaki ifadeyi açınız)
A  B C=[A’B’+AB] C
=(A’B’+AB)C’+(A’B’+AB)’C
=(A’B’+AB)C’+((A+B).(A’+B’))C
=A’B’C’+ABC’+A’BC+AB’C
=A(BC’+B’C)+A’(B’C’+BC)
=A(BC)+A’(BC)
=B(AC)+B’(AC)
=C(AB)+C’(AB)

Prof. Mehmet Akbaba Digital Logic 23


CONSENSUS THEOREM
The consensus theorem is very useful in simplifying
Boolean expressions. Given an expression of the form
XY + X' Z + YZ, the term YZ is redundant and can be elimi-

nated to form the equivalent expression XY + X' Z.


The term that was eliminated is referred to as the
consensus term. Given a pair of terms for which a
variable appears in one term and the complement of that
variable in another, the consensus term is formed by
multiplying the two original terms together, leaving out
the selected variable and its complement.

Prof. Mehmet Akbaba Digital Logic 24


For example, the consensus of ab and a' c is bc.
Also the consensus of abd and b'de' is (ad)(de') =
ade'. The consensus of terms ab'd and a' bd' is 0.

The consensus theorem can be stated as follows:


XY + X'Z + YZ = XY + X'Z

Proof:
XY + X'Z + YZ = XY + X'Z + (X + X')YZ
= (XY + XYZ) + (X'Z + X'YZ)
= XY(1 + Z) + X'Z(1 + Y) = XY + X'Z

Prof. Mehmet Akbaba Digital Logic 25


The consensus theorem can be used to eliminate
redundant terms from Boolean expressions. For example,
in the following expression, b' c is the consensus of
a' b' and ac, and ab is the consensus of
ac and bc', so both consensus terms can be eliminated:
(a’b’+ac+b’c=a’b’+ac and ac+bc’+ab=ac+bc’)

Prof. Mehmet Akbaba Digital Logic 26


The brackets indicate how the consensus terms are formed.
The dual form of the consensus theorem is:
(X+Y)(X’+Z)(Y+Z)=(X+Y)(X’+Z) (4.9)

Note again that the key to recognizing the consensus


term is to first find a pair of terms, one of which contains
a variable and the other its complement. In this case, the
consensus is formed by adding this pair of terms
together leaving out the selected variable and its
complement. In the following expression, (a + b + d') is a
consensus term and can be eliminated by using the dual
consensus theorem:

Prof. Mehmet Akbaba Digital Logic 27


The final result obtained by application of the consensus
theorem may depend on the order in which terms are
eliminated.
Example:
First, we eliminate BCD as shown. (Why can it be
eliminated?)
Now that BCD has been eliminated, it is no longer there,
and it cannot be used to eliminate another term. Checking
all pairs of terms shows that no additional terms can be
eliminated by the consensus theorem.
(4.10)
Prof. Mehmet Akbaba Digital Logic 28
This time, we do not eliminate BCD; instead we
eliminate two other terms by the consensus theorem.
After doing this, observe that BCD can no longer be
eliminated. Note that the expression reduces to four
terms if BCD is eliminated first, but that it can be reduced
to three terms if BCD is not eliminated.
(C and C’ also D and D’ is considered)

(4.11)

Prof. Mehmet Akbaba Digital Logic 29


Sometimes it is impossible to directly reduce an
expression to a minimum number of terms by
simply eliminating terms. It may be necessary to first
add a term using the consensus theorem and then
use the added term to eliminate other terms. For
example, consider the expression

F=ABCD+B’CDE+A’B’+BCE’
Consensus of ABCD+B’CDE (choosing variable B)
is ACDE. Adding this term gives:

F=ABCD+B’CDE+A’B’+BCE’+ACDE
Prof. Mehmet Akbaba Digital Logic 30
Now we can see that ABCD and B’CDE are consensus terms they
can be eliminated.
Then, we can eliminate ABCD and B'CDE using the
consensus theorem, and F reduces to:

F=A’B’+BCE’+ACDE
The term ACDE is no longer redundant and cannot be
eliminated from the final expression.

Prof. Mehmet Akbaba Digital Logic 31


Algebraic Simplification of Switching
Expressions
In this section we review and summarize methods for
simplifying switching expressions, using the laws and
theorems of Boolean algebra. This is important because

simplifying an expression reduces the cost of realizing


the expression using gates.

Later, we will learn graphical methods for simplifying


switching functions, but we will learn algebraic methods
first. In addition to multiplying out and factoring, three
basic ways of simplifying switching functions are
combining terms, eliminating terms, and eliminating
literals.

Prof. Mehmet Akbaba Digital Logic 32


1. Combining terms. Use the theorem XY + XY' = X to
combine two terms. For example,

abc’d’ +abcd’ =abd’ (X=abd’, Y=c) (4.12)


When combining terms by this theorem, the two terms to be
combined should contain exactly the same variables, and
exactly one of the variables should appear complemented
in one term and not in the other. Because X + X = X, a given
term may be duplicated and combined with two or more
other terms. For example,

ab’c+abc+a’bc=ab’c+abc+abc+a’bc=ac+bc
(=ac( b’+b )+bc( a+a’ )=ac+bc)

Prof. Mehmet Akbaba Digital Logic 33


The theorem still can be used, of course, when X and Y
are replaced with more complicated expressions.
For example, (Notice that (a+bc)’=a’(b’+c’) X=a+bc
X’=a’(b’+c’) X+X’=1 has been used)

(a+bc)(d+e’)+a’(b’+c’)(d+e’)=d+e’
=(d+e’)[(a+bc)+a’(b’+c’)]=d+e’
2. Eliminating terms. Use the theorem X + XY = X to
eliminate redundant terms if possible; then try to apply
the consensus theorem (XY + X' Z + YZ = XY + X' Z) to
eliminate any consensus terms. For example,

Prof. Mehmet Akbaba Digital Logic 34


a’b+a’bc=a’b (X=a’b)

a’bc’+bcd+a’bd=a’bc’+bcd
(X=c, Y=bd, Z=a’b)
(consensus theorem)
[=a’b c’ +b c d + a’bbd = a’bc’+bcd)]
(b=bb)

Prof. Mehmet Akbaba Digital Logic 35


Eliminating literals. Use the theorem X + X' Y = X +
Y to eliminate redundant literals. Simple factoring may
be necessary before the theorem is applied.
Example: (B+B’C’D’=(B+B’)(B+C’D’)=B+C’D)

A’B+A’B’C’+ABCD’=A’(B+B’C’)+ABCD’
=A’(B+C’D’)+ABCD’
=B(A’+ACD’)+A’C’D’
=B(A’+CD’)+A’C’D’
=A’B+BCD’+A’C’D’

Prof. Mehmet Akbaba Digital Logic 36


The expression obtained after applying steps 1, 2, and 3
will not necessarily have a minimum number of terms or a
minimum number of literals. If it does not and no further
simplification can be made using steps 1,2, and 3, the
deliberate introduction of redundant terms may be
necessary before further simplification can be made.

4. Adding redundant terms. Redundant terms can be


introduced in several ways such as adding xx',
multiplying by (x + x'), adding yz to xy + x' Z, or adding xy
to x. When possible, the added terms should be chosen
so that they will combine with or eliminate other terms.

Prof. Mehmet Akbaba Digital Logic 37


Example

(4.13)

The following comprehensive example illustrates the


use of all four methods:

Prof. Mehmet Akbaba Digital Logic 38


ACD’

(4.14)

What theorems were used in steps 1,2,3, and 4

Prof. Mehmet Akbaba Digital Logic 39


If the simplified expression is to be left in a product-of-
sums form instead of a sum-of-products form, the duals
of the preceding theorems should be applied.

(4.15)

What theorems were used in steps 1,2, and 3?


In general, there is no easy way of determining when a
Boolean expression has a minimum number of terms or a
minimum number of literals. Systematic methods for
finding minimum sum-of-products and minimum product-
of-sums expressions will be discussed in coming
chapters.

Prof. Mehmet Akbaba Digital Logic 40


REFEENCES»

• 1. Prof. M. Akbaba Mantık Devreleri


Notları
• 2. Hüseyin EKİZ, Mantık Devreleri,
Değişim Yayınları, 4. Baskı, 2005
• 3 .Thomas L. Floyd, Digital
Fundamentals, Prentice-Hall Inc. New
Jersey, 2006
• 4 .M. Morris Mano, Michael D. Ciletti,
Digital Design, Prentice-Hall, Inc.,New
Jersey, 1997

04/27/2023

You might also like